Perceived stress correlates with visceral obesity and lipid parameters of the metabolic syndrome: A systematic review and meta-analysis. (September 2018) - Tenk, Judit; Mátrai, Péter; Hegyi, Péter; Rostás, Ildikó; Garami, András; Szabó, Imre; Hartmann, Petra; Pétervári, Erika; Czopf, László; Hussain, Alizadeh; Simon, Mária; Szujó, Szabina; et al.
Highlights: Perceived stress shows correlation with visceral obesity and dyslipidemia. Perceived stress appears to be associated with increased diastolic blood pressure. Job-stress also correlates with higher fasting glucose level. Metabolic syndrome does not correlate with perceived stress of patients. Abstract: Background: Perceived stress has been proposed as a risk factor of metabolic syndrome. However, correlations between perceived stress and parameters of the metabolic syndrome have not been properly analyzed despite extensive research data on the topic. Our current meta-analysis aimed to examine the mutual association between perceived stress of patients and parameters of metabolic syndrome. Methods: This systematic review has been registered on the PROSPERO database (registration number CRD42017055293). Eligible studies divided participants based on their stress level or on the presence of metabolic syndrome. They reported at least one parameter of the metabolic syndrome or the stress level of the participants measured with some stress scale. Data from 17 articles met the eligibility criteria and were included. Random effects model with the DerSimonian and Laird weighting methods was applied. I-squared indicator and Q test were performed to assess heterogeneity. Results: Although the majority of individual studies failed to demonstrate correlations between stress and their analyzed parameters of metabolic syndrome, our meta-analysis showed a significant association between stress and BMI [average effect size (ES) with 95% confidence interval (95%CI), ES = 0.65, 95%CI 0.16, 1.14), waist circumference (ES = 1.84 cm, 95%CI 0.79, 2.89) and serum triglyceride level (ES = 7.52 mg/dl, 95%CI 0.07, 14.96). Additional analysis confirmed effects of stress on serum HDL (ES = - 1.699 mg/dl, 95%CI −2.966, −0.432) and diastolic blood pressure (ES = 1.04 mmHg, 95%CI 0.18, 1.89). No correlations were found for fasting glucose or systolic blood pressure. No association between metabolic syndrome and stress level of patients was detected either. Conclusion: The potentially key role of visceral obesity in the association between perceived stress and dyslipidemia or diastolic blood pressure are discussed together with potential moderators (e.g. gender-differences, variations in stress assessment and metabolic syndrome criteria) that may explain the inconsistent, contradictory results of the individual studies.